ON THE MORTALITY OF CARP FRY IN NURSERY PONDS AND THE ROLE OF PLANKTON IN THEIR SURVIVAL AND GROWTH - Alikunhi, K H; Chaudhury, H; Ramachandran, V (Indian Journal of Fisheries, 2016)
A critical study of the existing practices of fry collection, conditioning, transport and stocking at Cuttack, Orissa, has been made, and die possible sources of injury to and causes of mortality of the tender carp fry during these operations have been indicated